SOCIO-ECONOMIC DETERMINANTS OF E-WALLET USAGE AMONG UNORGANIZED RETAILERS IN BHANDARA DISTRICT - Dongardiveprav, Roshan Raibhanji; Deshmukh, Meena Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid spread of digital payment systems in India is bringing about a major transformation in retail trade. However, its adoption among unorganized retailers in rural and semi-urban areas is still not uniform. The present study has analyzed the socio-economic factors affecting the use of e-wallet among such unorganized retailers in Bhandara district of Maharashtra state. For the research, data from a total of 300 small retail traders in urban and rural areas was collected in a structured manner. Based on this information, a study was conducted to examine how factors such as age, education, income level, shop size, availability of smartphones and internet access affect e-wallet adoption. Logistic regression analysis revealed that higher education level, higher monthly turnover and regular internet access increase the likelihood of using e-wallets. In contrast, factors such as age, gender and rural location have little impact when it comes to digital readiness. In addition, some key barriers have also been identified - such as lack of digital literacy, concerns about transaction security, and transaction fees. The study highlights the need for community-based awareness campaigns, infrastructure development and targeted digital literacy campaigns to promote digital transactions. Accordingly, the study contributes to the broader conversation on digital financial inclusion.